Domestication footprints anchor genomic regions of agronomic importance in soybeans. Issue 2 (19th October 2015) - Han, Yingpeng; Zhao, Xue; Liu, Dongyuan; Li, Yinghui; Lightfoot, David A.; Yang, Zhijiang; Zhao, Lin; Zhou, Gang; Wang, Zhikun; Huang, Long; Zhang, Zhiwu; Qiu, Lijuan; et al.
Summary: Present‐day soybeans consist of elite cultivars and landraces ( Glycine max, fully domesticated (FD)), annual wild type ( Glycine soja, nondomesticated (ND)), and semi‐wild type (semi‐domesticated (SD)). FD soybean originated in China, although the details of its domestication history remain obscure. More than 500 diverse soybean accessions were sequenced using specific‐locus amplified fragment sequencing (SLAF‐seq) to address fundamental questions regarding soybean domestication. In total, 64 141 single nucleotide polymorphisms (SNPs) with minor allele frequencies (MAFs) > 0.05 were found among the 512 tested accessions. The results indicated that the SD group is not a hybrid between the FD and ND groups. The initial domestication region was pinpointed to central China (demarcated by the Great Wall to the north and the Qinling Mountains to the south). A total of 800 highly differentiated genetic regions and > 140 selective sweeps were identified, and these were three‐ and twofold more likely, respectively, to encompass a known quantitative trait locus (QTL) than the rest of the soybean genome. Forty‐three potential quantitative trait nucleotides (QTNs; including 15 distinct traits) were identified by genome‐wide association mapping. The results of the present study should be beneficial for soybean improvement and provide insight into the genetic architecture of traits of agronomic importance.